Durabilitas Geopolymer Foam Concrete Terhadap Ketahanan Sulfat - Debby Sinta Devi; Marguan Fauzi; Belliana Syafitri; Agung Laksono (Jurnal Tekno Global, 2023)
ABSTRACT  Geopolymer is an inorganic polymer material which is rich in silica and alumina and undergoes a polymerization process. Geopolymer concrete is an innovative concrete by replacing some cement binders with industrial waste such as fly ash. In addition, the manufacture of foam concrete is widely used in industrial building construction, especially in the walls of earthquake buildings and energy-efficient buildings. Geopolymer foam concrete is a modification of geopolymer concrete with foam concrete. Geopolymer foam concrete is made by combining a geopolymer mixture in the form of a 14 Molar solution of NaOH and Na2SiO3 as an activator with a ratio of 2.5 and fly ash as a precursor, then adding foam formed from a foaming agent and water with a ratio of 1:20, 1:30, 1:40. The quality of the foam used in the mix for making concrete affects the specific gravity, compressive strength and durability of geopolymer foam concrete. The purpose of this study was to determine the structural ability of geopolymer foam concrete against environmental conditions exposed to sulfate by using several variations in the ratio of foaming agent and water. The results of the endurance test showed that the specimen after being exposed to sulfuric acid for 56 days had a decrease in the mass of the test object for the ratios of foaming agent and water 1:20, 1:30, 1:40 which were 7.64%, 7.90% and 8.56 %. The ratio of foaming agent and water in the manufacture of smaller foam indicates better specific gravity, compressive strength and durability against sulfate attack. Keywords: Geopolymer, fly ash, foam concrete, durability, sulfit acid   ABSTRAK  Geopolimer merupakan material polimer anorganik yang kaya akan silika dan alumina dan mengalami proses polimerisasi. Beton geopolimer adalah beton inovasi dengan mengganti sebagian bahan pengikat semen dengan limbah industri seperti fly ash. Selain itu, pembuatan beton busa banyak digunakan dalam konstruksi bangunan industri, terutama pada dinding bangunan gempa dan bangunan hemat energi. Geopolymer foam concrete merupakan modifikasi dari beton geopolimer dengan beton busa. Geopolymer foam concrete dibuat dengan menggabungkan campuran geopolimer berupa larutan 14 Molar NaOH dan Na2SiO3 sebagai aktivator dengan rasio perbandingan 2,5 dan fly ash sebagai prekursor, kemudian menambahkan busa yang terbentuk dari foaming agent dan air dengan rasio perbandingan 1:20, 1:30, 1:40. Kualitas busa yang digunakan dalam campuran pembuatan beton mempengaruhi berat jenis, kuat tekan dan durabilitas geopolymer foam concrete. Tujuan dari penelitian ini adalah untuk mengetahui kemampuan struktur geopolymer foam concrete terhadap kondisi lingkungan terpapar sulfat dengan menggunakan beberapa variasi rasio foaming agent dan air. Hasil uji ketahanan menunjukkan bahwa spesimen setelah terpapar asam sulfat selama 56 hari memiliki penurunan massa benda uji untuk rasio foaming agent dan air 1:20, 1:30, 1:40  adalah sebesar 7,64%,  7,90% dan 8,56%. Rasio foaming agent dan air pada pembuatan busa yang lebih kecil menunjukkan berat jenis, kuat tekan dan durabilitas yang lebih baik terhadap serangan sulfat.  Kata Kunci: Geopolimer, fly ash, beton busa, durabilitas, asam sulfat